2020
DOI: 10.1111/jace.17404
|View full text |Cite
|
Sign up to set email alerts
|

Determination of atomistic deformation of tricalcium silicate paste with high‐volume fly ash

Abstract: Supplementary cementitious materials (SCMs), such as blast-furnace slag, 1 fly ash (FA), 2 natural pozzolans, 3 calcined clays, 4 and silica fumes, 5 have been investigated as partial replacements for Portland cement (PC) in concrete mixes. FA, a by-product of coal, is one of the main SCMs, and has been studied extensively. 6 Using FA as a partial replacement for PC allows for recycling of the industrial by-products, effectively reduces carbon emissions from cement production, and confers durability to concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 87 publications
(209 reference statements)
1
4
0
Order By: Relevance
“…Recently, PDF analysis has proven a powerful analytical tool for understanding the structure of amorphous phases (e.g., silica fume, fly ash, alkali silica reaction gel, and geopolymers) over a wide range of length scales 11 . Our previous studies confirmed the nanostructural deformation of C–S–H in C 3 S paste 16,49 and C 3 S paste with high‐volume fly ash 30 via PDF analysis. In our work, the PDF analysis was based on the isotropic assumption.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Recently, PDF analysis has proven a powerful analytical tool for understanding the structure of amorphous phases (e.g., silica fume, fly ash, alkali silica reaction gel, and geopolymers) over a wide range of length scales 11 . Our previous studies confirmed the nanostructural deformation of C–S–H in C 3 S paste 16,49 and C 3 S paste with high‐volume fly ash 30 via PDF analysis. In our work, the PDF analysis was based on the isotropic assumption.…”
Section: Resultssupporting
confidence: 73%
“…In our work, the PDF analysis was based on the isotropic assumption. Although it is clear that the structural anisotropy strain under uniaxial loading should be considered, 50 the difference between isotropic and anisotropic analyses is negligible for metallic glasses 30,51 . In addition, it is still controversial whether C–S–H possesses intrinsically anisotropic properties or transversely isotropic properties owing to its imperfect structure 52 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, XRD is used to determine the CH content instead of the C–S–H content because CH has a hexagonal crystal structure that can be easily detected by XRD. In contrast, the C–S–H phase forms a semi-crystalline or amorphous phase, which limits the use of XRD as a detection technique [ 47 , 99 , 100 , 101 ]. In the crystallization patterns ( Figure 17 ), the diffraction peaks of CH were observed at 2θ = 17.9°, 28.6°, 34.1°, 47.1°, and 50.1° [ 47 ].…”
Section: Resultsmentioning
confidence: 99%